The effect of 12-week different training methods applied to badminton athletes on some basic motoric properties - Albayati, M. A. K.; Kaya, Y. (European Journal of Fitness, Nutrition and Sport Medicine Studies, 2022)
This study aimed to examine the effects of 12-week plyometric, elastic resistance and core strength training applied to badminton athletes on some basic motoric properties. For this purpose, 21 badminton players participated equally and randomly in plyometric (PG), elastic resistance elastic (EG) and core strength (CG) training groups. Each training group participated in the experimental training practice as well as badminton training three days a week for 12 weeks. One day before and after the 12-week period, vertical jump, agility, throwing a weighted ball, sit and lie down, hand grip, push-ups, back strength, standing long jump, 10m-50m speed, reaction tests as motoric features; with the clear, drop and smash tests as badminton basic technical skills were measured. The obtained data were analyzed with paired samples t-test for within-group analysis, one-way ANOVA and LSD post-hoc test for between-group analysis. Values were presented as mean, and standard deviation, and were analyzed at a significance level of 0.05. According to the data obtained in the study, there was a significant difference in favor of the posttests in the results of the vertical jump, agility t-test, hand grip strength test, standing long jump test and badminton drop technique test among the pre-post tests in the PG group (p<0.05); in the CG group, there was a significant difference in the results of the push-up test, back strength test, badminton clear technique test and badminton drop technique test in favor of the posttests (p<0.05); in the EG group, there was a significant difference in favor of the posttests in the results of the vertical jump, sit-reach flexibility test, push-up test, badminton clear technique test and badminton drop technique test (p<0.05). Among the groups, between the PG group and the EG and CG groups, in favor of the PG group; it was determined that there was a significant difference in back strength between the CG group and the EG and PG groups in favor of the CG group (p<0.05). As a result, plyometric training has positive effects on lower extremity strength and explosive power properties, core training has positive effects on trunk strength and elastic resistance band training has positive effects on both lower and upper extremity strength and explosive power properties; it can be said that these exercises applied at the same time can positively affect the basic techniques of badminton.